Pendampingan Belajar Untuk Meningkatkan Kemampuan Membaca Siswa Kelas I SDN Koeloda - Wau, Maria Patrisia; Sayangan, Yohanes Vianey; Kedhi, Maria Anjelina; Demu, Maria Antonilda; Resi, Wilhelmina; Wae, Anastasia (Civiliza Publishing, 2024)
Teacher assistance activities for students who have low reading abilities at the UPTD SD Negeri Koeloda school are activities carried out by teachers to accompany students who still have low reading abilities, especially in pronouncing letters and spelling words. The aim of this activity is to provide assistance to students who have low abilities, especially class I students at UPTD SD Negeri Koeloda in pronouncing letters, spelling letters, reading sentences and reading texts. The research method carried out was using the direct observation method which was carried out through mentoring activities carried out through mentoring activities by teachers which were carried out for 4 months. The results of this research are: the mentoring activities carried out for class I students at UPTD SD Negeri Koeloda had a positive impact on students who had low abilities so they could pronounce letters, spell words, read sentences and read texts well. Apart from that, the mentoring activities carried out can provide opportunities for teachers to play an important role so that students are able to perform and develop their ability to read well.